nab-Paclitaxel for the treatment of pancreatic cancer - Kim, George (Cancer Manag Res, 2017)
BACKGROUND: Nanoparticle albumin-bound paclitaxel (nab-P) plus gemcitabine (Gem) became a standard treatment option for metastatic pancreatic cancer (MPC) following positive results from a global phase III trial (MPACT). A large number of studies have now published results on the use of nab-P/Gem to treat advanced and early-stage disease, warranting a comprehensive review. The main goal of this systematic review is to summarize the efficacy and safety data of nab-P/Gem for the treatment of pancreatic cancer (PC). METHODS: This systematic review includes results from studies that either published results in a peer-reviewed journal or presented the results at a major oncology conference. RESULTS: Sixty-two studies were included (50 in the advanced/metastatic setting and 12 in the locally advanced setting). Most studies on the treatment of MPC were exclusively first line (33/50). Nevertheless, the studies in this review comprised a broad spectrum of patients, including those <65 and ≥65 years of age and those with a Karnofsky performance status of 70–100. Median overall survival (OS) in studies of nab-P/Gem in the advanced/metastatic setting ranged from 8.7 to 13.5 months. In addition, 15 studies of patients with advanced/metastatic PC examined nab-P/Gem as a backbone on which to add a variety of agents, including cancer stem cell inhibitors, stromal disrupting agents, and immune-modulating agents (median OS, 6.9–17 months). Ongoing trials are investigating nab-P/Gem with or without other agents across disease settings. DISCUSSION: Studies conducted after MPACT have demonstrated that nab-P/Gem is an effective regimen for the first-line treatment of MPC for a wide range of patients. Regimens using nab-P/Gem as a backbone on which to combine additional agents are being studied actively, particularly in the advanced disease setting. Ongoing studies will yield valuable insights on the utility of nab-P–containing regimens to improve patient outcomes in PC in both earlier-stage and advanced disease.